Preparing for the Pandemic: City Boards of Health and the Arrival of Cholera in Montreal, New York, and Philadelphia in 1832 - Osborne, John (Urban History Review / Revue d'histoire urbaine, 2008)
This paper compares the responses of city officials in Montreal, New York, and Philadelphia to the cholera epidemic of 1832. In the absence of a medical consensus on the cause or contagious nature of the disease, physicians recommended a variety of preventive/protective measures ranging from quarantine to isolation hospitals to city sanitation. Significantly, prejudices toward immigrants, the working class, and particular ethnic groups influenced the city leaders' response to the epidemic as much as the opinion of medical experts. Of the three cities, Philadelphia experienced the lowest death rate during the epidemic—a success that contemporaries attributed to the city's hygienic/sanitation program but was due to the clean supply of drinking water from the city's state-of-the-art waterworks.